Hubungan Antara Lama Jam Kerja dan Tingkat Kelelahan Pekerja di Galangan Kapal PT X Berdasarkan Pemeriksaan Kesehatan - Mareta, Ade Tria; Muhammad Faisal Fadhil (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Work in shipyards is characterized by high workload, intense physical activity, and extreme environmental conditions. These conditions have the potential to cause fatigue, which may negatively impact performance, health, and occupational safety. This study aims to analyze the relationship between working hours and the level of fatigue among shipyard workers at PT X in Surabaya. The research was conducted from June 10 to 18, 2025, involving 37 active workers as the population, with samples selected using simple random sampling. Data were collected through interviews, field observations, and health examinations, then analyzed using Pearson correlation test with Minitab 18 software. Fatigue was measured based on six indicators: physical exhaustion, decreased concentration, mood instability, persistent drowsiness, lack of enthusiasm, and forgetfulness. The analysis showed a very weak correlation between working hours and physical fatigue (r = -0.004; p = 0.982), and a similarly weak correlation with concentration (r = -0.268; p = 0.108). However, the lack of enthusiasm variable showed a significant correlation in the 12-hour work group (r = 0.348; p = 0.035). This indicates that work motivation is more sensitive to long working hours than physical complaints. The conclusion of this study highlights that extended working hours can reduce motivation and potentially trigger chronic fatigue.